2019
DOI: 10.1016/j.sdentj.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative informed consent for mandibular third molar surgeries: A survey analysis in a subset of dentists and oral surgeons in Saudi Arabia

Abstract: ObjectivesThe objective of this study was to identify patterns of obtaining preoperative informed consent from patients undergoing mandibular third molar surgeries, in a subset of general dentists and oral surgeons in Saudi Arabia, and to compare the consenting patterns based on the clinician’s rank, years of experience, place of work and gender.MethodsA prospective questionnaire based study was designed and data was obtained through an online survey from 102 participants who were selected for the study. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was stated that 29 dental complaints were documented, and only a single case had documented IC. [ 18 19 ] Alkindi[ 20 ] conducted a survey with 83 patients regarding IC practice in oral surgery, and it was found that about 80% of the sample mentioned that they obtain IC with 53% obtaining only verbal consent. Alkindi's sample consisted of 40% specialist dentists (oral surgeons), which may have added 80% to the use of IC.…”
Section: Introductionmentioning
confidence: 99%
“…It was stated that 29 dental complaints were documented, and only a single case had documented IC. [ 18 19 ] Alkindi[ 20 ] conducted a survey with 83 patients regarding IC practice in oral surgery, and it was found that about 80% of the sample mentioned that they obtain IC with 53% obtaining only verbal consent. Alkindi's sample consisted of 40% specialist dentists (oral surgeons), which may have added 80% to the use of IC.…”
Section: Introductionmentioning
confidence: 99%